SCIENTIFIC STUDY ON EFFECT OF CLIMATE CHANGE IN BANDA ACEH BEFORE AND AFTER TSUNAMI DISASTER - Rahmayani Rahmayani (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Banda Aceh is one of the cities located in Aceh and became the capital of Aceh province, Indonesia. As the center of government, Banda Aceh has become the center of all economic activity, political, social and cultural. Aceh province has a tropical climate. It means that in a year consisting of the dry season (March to August) and rainy season (September to February). After the tsunami disaster that happened seven years ago that is exactly on December 26, 2004, the tsunami disaster caused by the earthquake of 9.2 Richter scale in Samudera Indonesia (Indonesia Ocean) thus temperatures continue to rise in Aceh province. This disaster resulted in hundreds of thousands of inhabitants and destroyed more than 60% of the buildings of this city. Tsunami disaster in Aceh cause the temperature in the city of Banda Aceh rises continuously. The tidal waves that devastated the city of Banda Aceh not only destroyed the buildings and a lot of casualties but also damaged the vegetation. Because of the number of damaged and missing vegetation of cover land, the temperature in Banda Aceh and its surrounding has rose. It happens because there is no direct solar radiation barrier and absorption of CO2 by vegetation.Keywords: climate change, before tsunami disaster, after tsunami disaster